Up‐regulation of miR‐497 confers resistance to temozolomide in human glioma cells by targeting mTOR/Bcl‐2. (8th January 2017) - Zhu, Danhua; Tu, Ming; Zeng, Bo; Cai, Lin; Zheng, Weiming; Su, Zhipeng; Yu, Zhengquan
Abstract: The occurrence of an inherent or acquired resistance to temozolomide (TMZ) is a major burden for patients suffering from glioma. Recently, studies have demonstrated that microRNAs play an important role in the regulation of tumor properties in cancers. However, whether miR‐497 contributes to glioma resistance to chemotherapy is not fully understood. In this study, we showed that the expression of miR‐497 was markedly up‐regulated in TMZ‐resistant glioma cells; high miR‐497 expression level was associated with TMZ‐resistant phenotype of glioma cells. The down‐regulation of miR‐497 in glioma cells enhanced the apoptosis‐induction and growth inhibition effects of TMZ both in vitro and in vivo, whereas promotion of miR‐497 increased the chemosensitization of glioma cells to TMZ. The increased level of miR‐497 in TMZ‐resistant glioma cells was concurrent with the up‐regulation of insulin‐like growth factor 1 receptor (IGF1R)/insulin receptor substrate 1 (IRS1) pathway‐related proteins, that is, IGF1R, IRS1, mammalian target of rapamycin (mTOR), and Bcl‐2. In addition, the knockdown of mTOR and Bcl‐2 reduced the tolerance of glioma cells to TMZ. Our results demonstrated that overexpression of miR‐497 is significantly correlated with TMZ resistance in glioma cells by regulating the IGF1R/IRS1 pathway. Therefore, miR‐497 may be used as a new target for treatment of chemotherapy‐resistant glioma. Abstract : The overexpression of miR‐497 is significantly correlated with temozolomide resistance in glioma cells by regulating mammalian target of rapamycin (mTOR)/Bcl‐2, and miR‐497 may be used as a new target for treatment of chemotherapy‐resistant glioma.